Rancang Bangun Sistem Informasi Manajemen Aset pada Universitas Pamulang Berbasis Web - Joko Riyanto (Teknik Informatika Universitas Pamulang, 2019)
Pamulang University is a successful and growing private university located in South Tangerang City. Of course, University of Pamulang has many assets to support its activities. But currently the University of Pamulang does not yet have an internal information system to control the assets owned. There is no asset management information system that will certainly experience difficulties in tracking asset data. Solution to overcome existing problems, of course, it requires an asset management information system that can run asset management more efficiently and structured, and facilitate the data collection of assets, data collection of assets based on their conditions, grouping assets based on their types and making it easier to search asset data. The system development used is waterfall. This model consists of requirement analysis, system and software design, implementation and unit system, system testing, operation and maintenance. The tools used in this research are Windows 10 pro 64 bit operating system, sublime text 3, and the database used as data storage is XAMPP. The final results of this research resulted in an Asset Management Information System at the Web-Based University of Pamulang.